(untitled) (International Journal of Engineering and Computer Science, 2014)
We present an strategy and a program to let instructors observe several main reasons relevant to on the internet assessments, such as student actions and analyze excellent. The strategy includes the signing of essential info relevant to student connections with the program during the performance of on the internet assessments and uses information creation to emphasize information useful to let instructors review and improve the whole evaluation process. We have focused on the development of actions styles of students and conceptual connections among analyze items. Furthermore, we have led several tests in our staff in order to evaluate the whole strategy. In particular, by assessing the information creation maps, we have recognized several previously unknown analyze strategies used by the students. Last, we have recognized several connections among questions, which gave us useful reviews on the analyze excellent.